Case report: Selpercatinib in the treatment of RET fusion-positive advanced lung adenocarcinoma: a challenging clinical case - Pagliaro, Raffaella; Medusa, Paola Maria; Vitiello, Fabiana; Aronne, Luigi; Campbell, Susan F. M.; Perrotta, Fabio; Bianco, Andrea (Frontiers in Oncology, 2025)
BackgroundRearranged during transfection (RET) fusions represent a distinct molecular subset of non-small cell lung cancer (NSCLC) with targeted therapeutic potential. Selpercatinib, a highly selective RET inhibitor, has demonstrated efficacy in various solid tumors harboring RET alterations. Here, we present a case highlighting the use and clinical outcomes of selpercatinib in a patient diagnosed with advanced lung adenocarcinoma harboring a RET fusion.Case presentationA 59-year-old woman with a history of stage IV lung adenocarcinoma harboring a KIF5B-RET fusion presented with disease progression following first-line chemo-immunotherapy. Selpercatinib was initiated as a targeted therapy, leading to a notable radiographic response and clinical improvement. The patient experienced a significant reduction in tumor burden and reported improved symptom control, with no significant adverse effects during the 21-month follow-up period.ConclusionsThis case highlights the efficacy and tolerability of selpercatinib in treating advanced lung adenocarcinoma with a RET fusion. The observed clinical response supports the early use of selpercatinib as a targeted therapy for RET fusion-positive NSCLC, including in patients with compromised general and respiratory conditions, especially in cases refractory to conventional treatments. Long-term follow-up studies are warranted to validate these findings and assess the durability of responses.